2015
DOI: 10.1007/s11255-015-1029-6
|View full text |Cite
|
Sign up to set email alerts
|

Is histological prostate inflammation in an initial prostate biopsy a predictor of prostate cancer on repeat biopsy?

Abstract: A histological inflammatory finding at the initial prostate biopsy was negatively associated with prostate cancer detection in repeat biopsy. This result could be useful to determine the need for repeat prostate biopsy in patients with persistently elevated prostate-specific antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Studies have shown that the presence of infiltrating immune cells in prostatic tissues is inversely correlated to PCa progression [203,204]. Prostatic inflammation, experimentally induced by intra-prostatic injection of formalin, leads to increased NRLP1 expression and consequent increase in IL-1β, IL-18 and caspase-1 levels [205].…”
Section: Impact Of Nlrs On Cancermentioning
confidence: 99%
“…Studies have shown that the presence of infiltrating immune cells in prostatic tissues is inversely correlated to PCa progression [203,204]. Prostatic inflammation, experimentally induced by intra-prostatic injection of formalin, leads to increased NRLP1 expression and consequent increase in IL-1β, IL-18 and caspase-1 levels [205].…”
Section: Impact Of Nlrs On Cancermentioning
confidence: 99%
“…1,2 Moreover, several studies found no association between inflammation and PCa. [3][4][5][6] Given the multitude of studies showing mixed results, we sought to perform a systematic review and meta-analysis of studies evaluating the association of prostate inflammation in PNB and the diagnosis of PCa among adult males. We hypothesize that any inflammation (chronic or acute) on PNB is associated with an increased risk of PCa diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In a Finnish prostate cancer screening trial, histologic inflammation in prostate biopsy among men with initially elevated serum prostate-specific antigen (PSA) was not linked to increased risk of prostate cancer [ 17 ]. Additionally, histological inflammatory finding at the initial prostate biopsy was negatively associated with prostate cancer detection in repeat biopsy [ 18 ]. When we consider the aggressiveness of prostate cancer among different ethnicities, African American (AA) men are at a higher risk and carry an aggressive load of disease.…”
Section: Prostate and Inflammationmentioning
confidence: 99%